Determination of carbamate pesticide in food using a biosensor based on reduced graphene oxide and acetylcholinesterase enzyme - da Silva, Martin K.L. [UNESP] (2018)
Food safety is a major concern for human health and wellbeing all over the world. A novel and sensitive biosensor based on reduced graphene oxide (rGO) and the enzyme acetylcholinesterase (AChE) was developed and applied for the detection of carbaryl in food samples. The glassy carbon/rGO/AChE biosensor was characterized morphologically and electrochemically using scanning electron microscopy and cyclic voltammetry/electrochemical impedance spectroscopy, respectively. Optimum differential pulse voltammetry conditions led to a nanomolar detection limit, and determination of carbaryl in tomato was achieved.